Determinants of persistent organic pollutant (POP) concentrations in human breast milk of a cross-sectional sample of primiparous mothers in Belgium. (October 2019) - Aerts, Raf; Van Overmeire, Ilse; Colles, Ann; Andjelković, Mirjana; Malarvannan, Govindan; Poma, Giulia; Den Hond, Elly; Van de Mieroop, Els; Dewolf, Marie-Christine; Charlet, François; Van Nieuwenhuyse, An; Van Loco, Joris; et al.
Abstract: Background: Bio-accumulation of persistent organic pollutants (POPs) in the environment and in the food chain can lead to high pollutant concentrations in human fat-containing tissues and breast milk. Objectives: We aimed to identify the maternal characteristics that determined POP concentrations in breast milk of primiparous mothers in Belgium. Methods: Breast milk samples were obtained from a cross-sectional sample of 206 primiparous mothers in 2014. POP concentrations in breast milk samples were determined by GC-ECNI-MS and GC-EI-MS/MS depending on the analytes' sensitivity. Associations between POP concentrations in breast milk and potential determinants were investigated using two-way contingency tables and multivariable generalized linear models. Results: Fifteen of the 23 screened POPs were detected in the breast milk samples. Four organochlorine compounds ( p, p ′-DDT, p, p ′-DDE, HCB and β-HCH) and two brominated flame retardant congeners (BDE-47, BDE-153) were detected at concentrations above the limit of quantification in >50% of the breast milk samples. Maternal age and BMI were usually associated with higher POP concentrations. Rural residency and consumption of home-produced eggs, fatty fish and fish oil supplements were associated with higher concentrations of DDT and DDE. Consumption of fatty fish and being breastfed during childhood were associated with higher concentrations of HCB and β-HCH. Fish oil supplements and home-produced eggs were associated with higher concentrations of BDEs, but for BDE congeners exposure routes other than diet require further investigation. Conclusions: Dietary and non-dietary determinants predict individual POP concentrations in breast milk. Graphical abstract: Unlabelled Image Highlights: Multicenter study of breast milk of 206 primiparous mothers in Belgium. POPs were measured following protocol of WHO-coordinated surveys on POPs. DDT, DDE, HCB, β-HCH, BDEs were detected in >50% of milk samples. POP levels were associated with diet, age, residence and childhood nursing. Dietary and non-dietary determinants can predict POP concentrations in breast milk.